Biology of Isopisthus parvipinnis: an abundant sciaenid species captured bycatch during sea-bob shrimp fishery in Brazil - Romero, Renato M. [UNESP]; Moraes, Leonardo E.; Santos, Marcella N.; Rocha, Gecely R. A.; Cetra, Mauricio (Sociedade Brasileira de Ictiologia, 2008)
A pesca de arrasto é o método mais comum de captura de camarão. Esta técnica causa impactos negativos na fauna demersal devido ao grande número de animais que são capturados acidentalmente e que geralmente são devolvidos mortos ao mar. As conseqüências desta metodologia de pesca e os aspectos biológicos das espécies envolvidas são pouco estudados, especialmente no Nordeste do Brasil. Este estudo tem como objetivo mostrar aspectos biológicos de Isopisthus parvipinnis (tortinha) capturada como fauna acompanhante da pesca do camarão sete barbas (Xiphopenaeus kroyeri) na região de Ilhéus, no estado da Bahia, Brasil. Um total de 1290 indivíduos foram capturados em coletas mensais, em três pontos de coleta distintos, de março de 2003 a fevereiro de 2005. O índice de dispersão de Morisita padronizado sugere que a espécie, na área analisada, apresenta uma distribuição agregada. O número de indivíduos variou significativamente entre as estações do ano (p < 0,0001), sendo maior durante o inverno. O comprimento estimado de primeira maturação (L50) foi de 159 mm, sendo que 95% dos indivíduos capturados estavam abaixo deste valor. A razão sexual encontrada foi de 1,5 machos para cada fêmea. Quanto à dieta, foram identificadas 10 categorias alimentares, sendo que Decapoda Dendobranchiata foi a mais importante em freqüência numérica e de ocorrência. Este fato sugere que Isopisthus parvipinnis é uma espécie carnívora, com tendência a carcinofagia, ao menos nos indivíduos jovens.

Trawling is the most common method of shrimp harvesting. This technique causes a negative impact on the fauna due to the high bycatch rates and to the animals that are accidentally caught and generally returned to the sea dead. The consequences of this technique and the biological aspects of the involved species are poorly studied, specially in the Brazilian northeast. The objective of this study was to show some aspects of the population biology of Isopisthus parvipinnis (Bigtooth corvina) captured as bycatch during sea-bob (Xiphopenaeus kroyeri) shrimp fishing in the region of Ilhéus, in the state of Bahia in Brazil. A total of 1290 individuals were caught in a monthly sampling at three different stations, from March, 2003 to February, 2005. The standardized Morisita index of dispersion suggests that this species has a clumped distribution in the studied area. The number of individuals showed a significant variation (p < 0.0001) between the seasons, being higher during the winter. The estimated first maturation length (L50) was about 159 mm, and 95% of the captured individuals were below this value. The sexual ratio found was 1.5 males for each female. Concerning to diet, 10 feeding categories were identified, and Decapoda Dendobranchiata was the most important in numeric frequency and occurrence. This fact suggests that Isopisthus parvipinnis is a carnivorous species, with a tendency toward crustacean-eating at least in the younger individuals.
Keywords: Biometric relationships; Inner shelf; Brazilian northeast